Digestion of beta-carotene loaded oleogels and transepithelial transport: in-vitro study - Martins, Artur J. (2018)
performance as carriers of bioactives, and their behaviour under gastrointestinal conditions has been scarcely studied. This work reports the behaviour of two distinct edible oleogels, loaded with a bioactive compound under in-vitro digestion conditions and assesses the bioactive bioacessibility and bioavailability of the bioactive compound. Method(s) and Results: Two types of gelation were used for the production of oleogels (i.e. single- and multi-component gelation), using respectively beeswax and a sterol mixture of gamma-oryzanol and beta-sitosterol (60X40 ratio). For both cases, long chain triglycerides were structured with 8% (w/w) of gelator and loaded with 0.1% (w/w) of beta-carotene. The recorded average hardness of sterol-based oleogels was approximately 4-fold higher than for beeswax oleogels. In-vitro digestion of oleogels was evaluated following the INFOGEST protocol. Bioacessibility of beta-carotene was of approx. 26% for sterol-based oleogels and close to 20% for beeswax-based oleogels. Afterwards, the digested samples were placed in contact with a monolayer of differentiated Caco-2 and HT-29-MTX cells, to determine the transepithelial transport of beta-carotene (bioavailability). Sterol gels favor the bioavailability of beta-carotene with an increase of 15% of bioactive transport over beeswax-based oleogels. No cytotoxicity of oleogels was detected. Conclusions: This study shows that the INFOGEST standard protocol is suitable for the in-vitro digestion evaluation of oleogels and that the bioacessibility of beta-carotene in these systems lays between 20 and 26 %. Oleogels are able to carry beta-carotene through the digestive process being enhanced by sterol gels.